KLASIFIKASI AYAT-AYAT HUKUM (DARI SEGI QATH`I DAN ZHANNI) - Subhan, Subhan (Mazahib, 2013)
Qur’an from al-tsubut view is qath’i.  Qath’i disavowal will bring theologies consequencies.  However, from al-dalalah view, Qur’an verses are some qath’i and others zhanni.  Qath’i al-dalalah is a permanence that point to particular meaning that not contain possibility to be ta’wil or far away from original meaning and there is no space or opportunity to understand besides it.  At the same time zhanni al-dalalah is that still contain two or more probability.